1991
DOI: 10.3109/00365599109024551
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Hemodialysis Patients

Abstract: Twenty-nine hemodialysis patients were studied to evaluate different laboratory measures in assessing muscle protein stores and detecting protein malnutrition. Arm muscle circumference (AMC) was used as a reference for somatic protein stores. AMC correlated with serum complement C3, plasma histidine, isoleucine, leucine, methionine and threonine concentrations as well as with body mass index. The lowest quartile of AMC was found most reliably by measuring plasma methionine, histidine, leucine and isoleucine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
3

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 7 publications
1
22
1
3
Order By: Relevance
“…Although the etiology of malnutrition in HD patients is multifactorial, decreased oral intake because of loss of appetite, severe dietary protein restriction and increased catabolism resulting from insufficient HD therapy seem to be the commonest factors [1, 2, 3, 4, 5, 6, 7]. Furthermore, social and economic factors may also play an important role in the development of malnutrition in HD patients [2, 4, 8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology of malnutrition in HD patients is multifactorial, decreased oral intake because of loss of appetite, severe dietary protein restriction and increased catabolism resulting from insufficient HD therapy seem to be the commonest factors [1, 2, 3, 4, 5, 6, 7]. Furthermore, social and economic factors may also play an important role in the development of malnutrition in HD patients [2, 4, 8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…11,42 The main biochemical parameters suggestive of protein-energy malnutrition in dialysis, such as serum albumin, dietary protein intake (indicated by the protein equivalent of total nitrogen appearance or PCR) and predialysis serum urea nitrogen correlate with morbidity or mortality, 4,5,11 these markers, however, must be interpreted with caution and, more important, alterations of such indexes often become manifest only late in the course of the deteriorating nutritional status in dialysis, that is, after severe malnutrition is established. 6,11,12 Bioelectrical impedance analysis (BIA) allows a fast and sensitive bedside assessment of human body composition. 14,21 The tetrapolar bioelectrical impedance analysis described by Shizgal and Jodin et al refers to a three-compartment model body cell mass (BCM), body fat (FM), and extracellular mass (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…In dialysis, mild to moderate malnutrition is not revealed by abnormalities of the common nutritional markers that become manifest only in the advanced stage of disease; 6,11,12 consequently, practical and sensible indicators of body composition are needed for clinical purposes. Most of the available methods for evaluating body composition, even though accurate, cannot easily be used in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Serum transthyretin, also known as thyroxine-binding prealbumin or prealbumin, has been proposed as an early indicator of nutritional status in hemodialysis patients (4,6,13,14). In studies involving hemodialysis patients, transthyretin levels have been found to correlate Goldwasser et a.…”
Section: Transthyretin Levels and Nutritional Statusmentioning
confidence: 99%
“…These findings are in agreement with Vehe et al (21) where transthyretin correlated significantly with cumulative intakes of both protein and energy, in chronic renal failure patients receiving nutrition support. Transthyretin has been found to correlate with other markers of body mass such as the midarm muscle circumference (4,13,20) and triceps skinfold thickness (4,20).…”
Section: And 2 4 Nfdltmentioning
confidence: 99%